Resonance Raman detection of the Fe2+-C-N modes in heme-copper oxidases: a probe of the active site - Pinakoulaki, Eftychia; Vamvouka, Magdalini; Varotsis, Constantinos (My University, 2004)
Resonance Raman spectroscopy has been employed to investigate the reduced cyano complexes of cytochrome aa3 from bovine heart and Rhodobacter sphaeroides and of cytochrome bo3 from E. coli. In the aa 3-type oxidases, the frequency of the Fe-CN stretching mode is located at 468 cm-1, and the bending Fe-C-N vibration, at 500 cm -1. The fully reduced cytochrome bo3-CN complex gives rise to a stretching vibration at 468 cm-1, a bending vibration at 491 cm-1, and a stretching C-N vibration at 2037 cm-1. The observed differences between aa3 and bo3 oxidases in the frequencies of the Fe-C-N group suggest a quantitative difference in the structure of the His-heme a32+/CuB1+ and His-heme o32+/CuB1+ binuclear pockets upon CN- binding
Keywords: Copper; Heme; Iron; Cattle; Raman spectrometry; Vibration; Enzymes; Cytochromes; Spectrum analysis